Paratracheal air cyst and bronchogenic cyst in patients with esophageal cancer who received thoracoscopic esophagectomy: A case series of three patients. (August 2021) - Okumura, Tomoyuki; Miwa, Takeshi; Watanabe, Toru; Akashi, Takahisa; Nomoto, Kazuhiro; Kimura, Nana; Takeda, Naoya; Uotani, Tomofumi; Baba, Hayato; Hirano, Katsuhisa; Shibuya, Kazuto; Hashimoto, Isaya; et al.
Abstract: Introduction and importance: Mediastinal cystic lesions, such as paratracheal air cyst (PTAC) and bronchogenic cyst (BC), are rare anomaly usually found incidentally in thoracic imaging. Special attention is needed in the case of thoracic surgery. Case presentation: All three patients were male, 71, 73, and 76 years old. Preoperative CT showed each had a lobular cystic lesion at the right posterolateral side of trachea in the thoracic outlet 11, 14, and 19 mm in size, respectively, with air density and tracheal communication, leading to a diagnosis of PTACs. An oval cystic lesion, 7 mm in size, was found in one patient at the right lateral side of the upper esophagus with low density and without tracheal communication, leading to a diagnosis of paraesophageal BC. Intraoperative findings of the three PTACs demonstrated a soft bulge from the membranous portion of trachea that was left intact. The BC had an oval elastic structure, mimicking a metastatic lymph node, and was removed with the mediastinal lymph nodes. Histological examination showed ciliated columnar epithelium, confirming a diagnosis of BC. Clinical discussion: PTACs are associated with increased intraluminal pressure due to chronic lung disease. BCs are congenital anomalies that originate from abnormal budding of the embryonic foregut. Conclusion: PTACs and BCs need to be considered in preoperative image diagnosis in patients with esophageal cancer. PTACs should be left intact to avoid tracheal injury, while removal of isolated BCs is recommended as a diagnostic and therapeutic measure. Highlights: Paratracheal air cyst (PTAC) and bronchogenic cyst (BC) are rare anomaly. Three PTACs and a BC were found in patients who received thoracoscopic esophagectomy for esophageal cancer. PTACs were carefully left intact to avoid tracheal injury. BC was removed for diagnostic and therapeutic measure. PTACs and BCs need to be considered in preoperative image diagnosis in patients with esophageal cancer.